Control of American Burnweed (Erechtites hieraciifolia) in Bermudagrass Turf. (December 2014) - Atkinson, Jeffrey L.; Cross, Robert B.; McCarty, Lambert B.; Estes, Alan G.
Abstract : American burnweed is an early successional summer annual species in the Asteraceae. This weed is a poor competitor; however, it rapidly colonizes disturbed and low-maintenance areas, especially following an environmental disturbance. Recently, turfgrass managers have made adjustments to maintenance practices to satisfy budget requirements and address environmental concerns. This has resulted in reduced mowing frequency in some golf course rough and out-of-play turf areas, and has allowed establishment of broadleaf weed species such as American burnweed which would otherwise be controlled by frequent mowing. The purpose of this study was to evaluate PRE and POST herbicide treatments for American burnweed control in an unmown bermudagrass golf course rough. Single PRE applications of simazine at 2.24 kg ai ha −1 and indaziflam at 0.06 kg ai ha −1 provided > 80% American burnweed control 24 wk after treatment (WAT) in 2012 and 2013. Sequential combination applications of liquid formulations of dimethenamid-p + pendimethalin (2.24 + 1.68 kg ai ha −1 ) provided 95% American burnweed control 24 wk after initial treatment in 2012 and 2013. Other PRE treatments did not provide consistent control of American burnweed across rating dates and years. Regardless of year, four POST treatments provided ≥ 87% control at 8 and 16 WAT. These included thiencarbazone + foramsulfuron + halosulfuron (0.02 + 0.044 + 0.07 kg ai ha −1 ), thiencarbazone + iodosulfuron + dicamba (0.02 + 0.15 + 0.005 kg ai ha −1 ), triclopyr + clopyralid (0.88 + 0.32 kg ai ha −1 ), and sulfentrazone + metsulfuron (0.4 + 0.04 kg ai ha −1 ). Several PRE and POST American burnweed control solutions exist for low maintenance bermudagrass areas. Future research should continue to screen other herbicides for control efficacy and focus on application timing to balance season-long control with minimal chemical inputs.